Understanding Long-Term Energy Use and Carbon Dioxide Emissions in the Usa - Richard S.J. Tol; Stephen W. Pacala; Robert Socolow (Fondazione Eni Enrico Mattei (FEEM), 2006)
We compile a database of energy uses, energy sources, and carbon dioxide emissions for the USA for the period 1850-2002. We use a model to extrapolate the missing observations on energy use by sector. Overall emission intensity rose between 1850 and 1917, and fell between 1917 and 2002. The leading cause for the rise in emission intensity was the switch from wood to coal, but population growth, economic growth, and electrification contributed as well. After 1917, population growth, economic growth and electrification pushed emissions up further, and there was no net shift from fossil to non-fossil energy sources. From 1850 to 2002, emissions were reduced by technological and behavioural change (particularly in transport, manufacturing and households), structural change in the economy, and a shift from coal to oil and gas. These trends are stronger than electrification, explaining the fall in emissions relative to GDP.
Keywords: Q5; Q4; Q0; 330; Carbon Dioxide Emissions; Decomposition; Environmental Kuznets Curve; USA; History; Energieträger; Energiekonsum; Kohlendioxid; USA